Transportation of Children and Young People with Disabilities to Educational Institutions - Kotulski, Mariusz (Acta Universitatis Lodziensis. Folia Iuridica, 2023)
The legislator imposed on communes the obligation to provide disabled students with free transport and care during transport to the nearest primary school, and students with physical disabilities, including aphasia, with moderate or severe intellectual disabilities – also to the nearest secondary school, until the end of the year in the calendar year in which the student turns 21, and in the case of children and youth with a profound intellectual disability (up to 25 years of age) and multiple disabilities, one of which is intellectual disability, as long as they attend a rehabilitation center upbringing (up to 24 years of age). The purpose of these regulations is to help families bringing up students with disabilities and to facilitate the fulfillment of the obligation of education by such people. Therefore, the legislator differentiated the obligation to provide free transport and care during the transport of disabled students to schools and other centers in terms of subjectivity, time and destination, depending on the type and degree of disability. This obligation may be fulfilled by the commune by organizing free transport and care during the transport of children, youth and schoolchildren, or by reimbursing the parents for the costs of transport – which takes place on the basis of an agreement concluded between the commune head and the parents of such a child. The choice of a specific method of fulfilling the obligation rests solely with the decision of the parents (legal guardians) of eligible children.